Impact and Legal Challenges of Artificial Intelligence Violating Human Rights: A Socio-Legal Study - Mohd Aamir Malik (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Artificial intelligence (AI) technologies have experienced a massive developmental process and have created unheard opportunities in several industries. But it has created a major alert related to plundering of basic human rights as well. Anthony M and Anthony have highlighted some of the issues with AI as bias in algorithms that endangers fair trial and equality, mass surveillance that imposes on privacy and freedom of expression. This socio-legal research examines the way the development of AI affects the protection of human rights and how the law in various states aces the challenge of addressing AI-generated rights infringements. Based on the concept of international human rights and the new jurisprudence, the research demonstrates an accountability, transparency and ethical protection regulation gap. It ends with a call to promote a humanistic vision of the law that would put innovation in line with respect of rights.